The Embeddedness of Organizations: Dialogue & Directions - Dacin, M. Tina; Ventresca, Marc J.; Beal, Brent D. (Journal of Management, 1999)
We review research on organizations to highlight prevailing and emerging conceptions for embeddedness. An integrated framework that considers the sources, mechanisms, outcomes, and strategic implications of embeddedness is presented. Also, promising research directions for embeddedness approaches, including cross-level issues (such as collective cognition and nesting), as well as issues related to temporality, networks, and methodology are identified.